A review of the consequences of complementary sex determination and diploid male production on mating failures in the Hymenoptera. Issue 1 (9th August 2012) - Harpur, Brock A.; Sobhani, Mona; Zayed, Amro
Abstract Complementary sex determination is the ancestral sex‐determination mechanism in the Hymenoptera. Under this system, diploid individuals develop into females if they are heterozygous at an autosomal sex‐determining locus or loci, whereas haploid individuals develop into males because they are hemizygous at the sex‐determining locus or loci. However, diploid males can still arise from fertilized eggs if such individuals are homozygous at the sex‐determining locus or loci. Diploid males are often viable but sire few daughters, thereby representing a substantial genetic load in hymenopteran populations. Here, we review the effects of complementary sex determination and diploid male production from the perspective of female hymenopterans. Because female hymenopterans need not mate to produce haploid sons, complementary sex determination can cause special forms of mating failures by preventing some females from controlling the sex ratio of their brood and producing the desired number of daughters. Under some circumstances, complementary sex determination can cause complete mating failure by preventing females from producing daughters altogether. Although we outline serious gaps of knowledge in the field, the data at hand suggest that diploid male production can substantially increase mating failures in small populations of economically and ecologically important hymenopterans.